A compound Ca‐, Al‐rich inclusion from CV3 chondrite Northwest Africa 3118: Implications for understanding processes during CAI formation. (20th August 2015) - Ivanova, Marina A.; Lorenz, Cyril A.; Krot, Alexander N.; MacPherson, Glenn J.
Abstract A calcium‐aluminum‐rich inclusion 3N from the Northwest Africa (NWA) 3118 CV3 carbonaceous chondrite is a unique cm‐sized compound object, primarily a forsterite‐bearing type B (FoB) CAI, that encloses at least 26 smaller CAIs of different types, including compact type A (CTA), B, C, and an ultra‐refractory inclusion. Relative to typical type A and B CAIs found elsewhere, the bulk compositions of the types A and B CAIs within 3N more closely match the bulk compositions predicted by equilibrium condensation of a gas of solar composition. Being trapped within the FoB melt may have protected them from melt evaporation that affected most "stand‐alone" CAIs. 3N originated either as an aggregate of many smaller (mostly types A, B, C) CAIs plus accreted Fo‐bearing material (like an amoeboid olivine aggregate) which experienced partial melting of the whole, or else as a FoB melt droplet that collided with and trapped many smaller solid CAIs. In the former case, 3N recorded the earliest accretion of pebble‐sized bodies known. In the latter case, the presence of a large number of individual refractory inclusions within 3N suggests a very high local density of refractory solids in the immediate region of the host CAI during the brief time while it was melted. Collisions would have occurred on time scales of hours at most, assuming a melt solidification interval for the host CAI of 300–400 °C (maximum) and a cooling rate of ~10 °C/h.